Uniqueness theorems for multiple lacunary trigonometric series - Volchkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
In a many-dimensional space, we study some properties of functions with lacunary Fourier series depending only on the values of these functions in a neighborhood of a certain point.